Lysis of bacterial cells in the process of bacteriophage release--canonical and newly discovered mechanisms - Woźnica, Wioleta M; Bigos, Joanna; Łobocka, Małgorzata B (Postȩpy higieny i medycyny doświadczalnej, 2015)
The release of phage progeny from an infected bacterium is necessary for the spread of infection. Only helical phages are secreted from a cell without causing its destruction. The release of remaining phages is correlated with bacterial lysis and death. Thus, the understanding of phage lytic functions is crucial for their use in the fight with bacterial pathogens. Bacteriophages with small RNA or DNA genomes encode single proteins which are called amurins and cause lysis by the inhibition of cell wall synthesis. Bacteriophages of double-stranded DNA genomes, which dominate in the environment, encode enzymes that are called endolysins and contribute to lysis by the cleavage of cell wall peptydoglycan. Endolysins that do not contain signal sequences cannot pass the cytoplasmic membrane by themselves. Their access to peptidoglycan is provided by membrane proteins - holins, which can form in the membrane large pores, that are called "holes". Some endolysins do not require holins for their transport, owing to the presence of the so called SAR sequence at their N-terminus. It enables their transport through the membrane by the bacterial sec system. However, it is not cleaved off, and thus these endolysins remain trapped in the membrane in an inactive form. Their release, which is correlated with the activation, occurs as a result of membrane depolarization and depends on proteins that are called pinholins. Pinholins form in membrane pores that are too small for the passage of endolysins but sufficient for membrane depolarization. Proteins that are called antiholins regulate the timing of lysis, through the blockage of holins action until the end of phage morphogenesis. Additionally, newly identified lytic proteins, spanins, participate in the release of progeny phages from Gram-negative bacteria cells. They cause the destruction of outer cell membrane by its spanning with the cytoplasmic membrane. This is possible after the endolysin-mediated destruction of peptidoglycan, which separates both membranes, and ensures the fast completion of lysis.